Soliton propagation in a medium with Kerr nonlinearity and resonant impurities: A variational approach - Caetano, D. P.; Cavalcanti, S. B.; Hickmann, J. M.; Kamchatnov, A. M.; Kraenkel, R. A. [UNESP]; Makarova, E. A. [UNESP] (American Physical Society (APS), 2003)
Using a variational approach we have studied the shape preserving coherent propagation of light pulses in a resonant dispersive medium in the presence of the Kerr nonlinearity. Within the framework of a combined nonintegrable system composed of one nonlinear Schrödinger and a pair of Bloch equations, we show the existence of a solitary wave. We have tested our analytical solution through numerical simulations confirming its solitary wave nature. © 2003 The American Physical Society.